THE SURFACE CHEMISTRY AND STRUCTURE OF ACID-LEACHED ALBITE: NEW INSIGHTS ON THE DISSOLUTION MECHANISM OF THE ALKALI FELDSPARS - Gout R.; Oelkers E.H.; Schott J.; Zwick A. (My University, 1997)
The surfaces of fresh albite crystals, and of albite crystals following their two hour leaching in an aqueous 0.3 molal HCl solution at a temperature of 200°C, were analyzed by Raman spectroscopy, scanning electron microscopy, and Energy Dispersive Spectroscopy (EDS). Scanning electron microscopy reveals that dissolution is nonuniform and reacted surfaces exhibit a range from fresh to extremely altered regions, the latter characterized by the presence of etch pits and crater-like structures. Energy dispersive spectroscopy indicates that the chemical composition of the near surface is heterogeneous; the most altered regions have significantly lower Na/Si and Al/Si ratios compared to both unreacted albite and the fresher appearing regions of reacted albite. This result demonstrates that (1) initial dissolution produces spatially discontinuous altered layers, and (2) the depletion of both alkali cations and aluminum from the near surface region is associated with locally enhanced alkali-feldspar dissolution. This latter observation is strong evidence that the inverse relationship observed between far from equilibrium constant temperature/pH alkali feldspar dissolution rates and aqueous alkali cation and/or aluminum concentration stems from a reaction mechanism involving the selective removal of these elements from the mineral structure. The Raman spectra of increasingly altered surface regions confirm that alkali feldspar dissolution is the result the sequential breaking of bonds in the mineral structure. A close correspondence is apparent between the Raman spectra of amorphous silica and the reacted albite's most altered regions. As altered layers on albite surfaces are discontinuous, the accurate determination of their thickness requires techniques which can distinguish chemical differences on a micron scale.